Laughter, creativity, and perseverance: female agency in Buddhism and Hinduism - Hüsken, Ute (Religion, culture, and history, 2022)
Introduction: Female Agency in Buddhist and Hindu Contexts / Ute Hüsken -- Section I. Renewing Religion in Female Spaces: 1.1. Exclusion, Secrecy and the (Under)ground: Dynamics of Female Religious and Ritual Agency in Kalmykia / Valeriya Gazizova --1.2. "This is not a Home, it is a Temple": Creative Agency in Navarāttitri Kolu / Ina Marie Lunde Ilkama -- Section II. Appropriation of Male Spaces: 2.1. Body-Politics and the Gendered Politics of Hindu Militancy: Shiv Sena Women and Political Agency in Western India / Tarini Bedi -- 2.2. Buddhist 'Radicalism': A Vehicle for Female Empowerment? / Melyn McKay & Iselin Frydenlund -- 2.3. Laughing on a Rooftop: Female Buddhist Agency as Local in Lumbini, Nepal / Amy Paris Langenberg -- 2.4. Right to Pray: A Comparative Analysis of Sabarimala and Śani / Shefali More -- Section III. Performing Religion Publicly: 3.1. Hindu Women and the Gendering of Religious and Ritual Authority in Trinidad / Priyanka Ramlakhan -- 3.2. Tradition, Innovation, and Resistance? Training Girls in Sanskrit and Vedic Rituals / Ute Hüsken -- 3.3. "I Will be the Śaṅkarācāryā for Women!": Gender, Agency, and a Guru's Quest for Equality in Hinduism / Antoinette Elizabeth DeNapoli -- Section IV. Research Strategies: 4. Female Agency in Buddhism and Hinduism: Methodological Reflections and Collective Commitments / Caroline Starkey.